Empathic Humanitarianism: Understanding the Motivations behind Humanitarian Work with Migrants at the US–Mexico Border. (March 2020) - Gomez, Ricardo; Newell, Bryce Clayton; Vannini, Sara
Executive Summary: The growing numbers of vulnerable migrants seeking shelter and refuge in the United States and Europe are finding increased racism and xenophobia as well as renewed efforts by humanitarian volunteers to offer them aid, sanctuary, and protection. This article sets forth a typology to better understand the motivations of volunteers working to help migrants in need of humanitarian assistance. Why do people go out of their way to offer humanitarian aid to someone they do not know and, in some cases, they will never meet? What are the drivers of altruistic behavior of humanitarian volunteers in the face of rising injustice, nationalism, and xenophobia? In answer to these questions, we offer a typology centered on empathic concern, differentiating secular/faith-based motivations, and deontological/moral-virtue motivations, with particular behaviors in each of the four resulting categories: the Missionary Type, the Good Samaritan Type, the Do Gooder Type, and the Activist Type. We also suggest four additional self-centered (non-altruistic, or not-other-centered) types (Militant, Crusader, Martyr, and Humanitarian Tourist). The nuances offered by this typology can help organizations working with migrants and refugees better understand and channel the enthusiasm of their volunteers and better meet the needs of the vulnerable populations they serve. This is especially important at a time when migration is being criminalized and when humanitarian aid is deemed unpatriotic, if not outright illegal. In the face of increased nationalistic and xenophobic messages surrounding migration, we need to articulate the altruistic humanitarian motivations of volunteers in the context of migration aid. Our typology may also be used to understand altruistic behaviors in other contexts such as disaster relief, community organization and activism, international adoptions, or organ donations to strangers, among others, in which altruistic empathic concern can be an important motivation driving people to act for the well-being of distant others.